Chemokines and their receptors: insights from molecular modeling and crystallography. (October 2016) - Kufareva, Irina
Graphical abstract: Highlights: Chemokine interactions with receptors trigger cell migration in immunity and cancer. 2015 brought high-resolution insights into the structural basis of these interactions. Complex architecture is conserved but features diverse, functionally distinct epitopes. Chemokine dimerization interfaces are repurposed for receptor binding. Novel epitopes hold promise for fine-tuned pharmacological modulation. Abstract : Chemokines are small secreted proteins that direct cell migration in development, immunity, inflammation, and cancer. They do so by binding and activating specific G protein coupled receptors on the surface of migrating cells. Despite the importance of receptor:chemokine interactions, their structural basis remained unclear for a long time. In 2015, the first atomic resolution insights were obtained with the publication of X-ray structures for two distantly related receptors bound to chemokines. In conjunction with experiment-guided molecular modeling, the structures suggest a conserved receptor:chemokine complex architecture, while highlighting the diverse details and functional roles of individual interaction epitopes. Novel findings promote the development and detailed structural interpretation of the canonical two-site hypothesis of receptor:chemokine recognition, and suggest new avenues for pharmacological modulation of chemokine receptors.